Análisis del impacto de las medidas tomadas por el covid-19 en la calidad del aire en colombia : el caso de bogotá y medellín (2020)
In Colombia, the monitoring and control of air quality has played an increasingly important role in recent years. On March 11, 2020, the WHO declared that there was a global pandemic of COVID-19, the first in history due to this type of virus. With this, in Colombia, there was evidence of a reduction in the use of different means of transportation and the closure of some industries where a reduction in emissions and, therefore, less pollution would be expected. For this work, the different concentrations of PM_2.5, CO, NO_x and O_3 were first analyzed since the beginning of the quarantine in the cities of Medellín and Bogotá. Daily averages were taken from January 1 to August 31, 2020 and information on fires and mobility was also acquired to develop a more detailed analysis. With data from the RMCAB, the SIATA of Medellín, FIRMS and IHME it was possible to find the correlations between the different pollutants to be analyzed and the fire and mobility factors. It was found that CO and NO_x concentrations are highly related to the change in mobility during the pandemic and, on the other hand, it was evidenced that PM_2.5 and O_3 are modulated by active fires in Colombia and Venezuela. Finally, each pollutant was compared with the current air quality regulations. With this, it was shown that in Bogotá and Medellín the maximum concentration allowed is exceeded in the months of March and early April. It was established that the main cause of this increase was due to the number of active fires at that time. In addition, it was inferred that the peak presented on June 25 and 26 was caused by the arrival of dust from the Sahara desert, which for those days greatly affected the poor air quality in the cities.